Strategy For The Development Of A School Plan At The Kesuma Elkaemde Namorambe Education Foundation - Mesiono Mesiono; Sri Rahayu Nasution; Azmar Azmar; Elfin Nazri (At-Tarbiyat, 2022)
There are often problems in the preparation of school development plans, starting with a lack of assistance, supervision, competence and unsystematic plans made. Thus, the purpose of this study was to describe the school development plan at the Kesuma Elkaemde Education Foundation. This research is a qualitative research. The subjects of this research are principals, teachers, and all other devices that take part in the preparation of school plans. The data collection technique of this research is by interview, observation and documentation. After that, the data were analyzed by examining the data that had been collected, namely data reduction, verification, and data presentation. The results show that the school development plan at the Kesuma Elkaemde Education Foundation implements a school development plan by carrying out a Short-Term Annual Program Strategy which includes the First Year Program (2018–2019), Second Year Program (2019–2020), Third Year Program (2020–2021 ), Fourth Year Program (2021–2022). In addition, there is also a 12-year Long-Term Program Strategy in the form of vision, mission and goals. And every development plan that is prepared is oriented to character and cultural education oriented to systems of thinking, values, morals and beliefs.